Study of the tightness of single seams of LOGICBASE™ / ECOBASE™ PVC membranes in engineering waterproofing systems - V. N. Shalimov; A. V. Tsybenko; I. N. Goglev; S. A. Loginova (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. Currently, engineering waterproofing systems with polymer waterproofing membranes are widely used at various construction structures. At the same time, the usage of polymer membranes implies the operation of break welds, the strength of which should be no less than the strength of the waterproofing material itself. The purpose of the study is to evaluate the water resistance of single seams (without test channels, welded by manual or automatic equipment) for LOGICBASE™ / ECOBASE™ grade V-SL polymer membranes at a pressure of 1 MPa. Method. Testing of waterproofing seams for water resistance is carried out according to the requirements of GOST EN 1928-2011, method B. The GESTER model GT-C26B hydrostatic pressure testing device is used as a test installation. LEISTER welding equipment of Varimat V2 (automatic equipment) and Triac AT (manual/hand equipment) models was used for welding samples. The width of the weld was at least 30 mm. Result. At a hydrostatic head pressure of 1 MPa, within 24 hours from the start of the test, there were no traces of water penetration in the samples, which indicates that the seams are completely waterproof. Conclusion. Single seams of LOGICBASE™/ECOBASE™ engineered waterproofing PVC membranes are completely sealed at 1 MPa water pressure.